NPWT in Complex Surgical Management of Combat Vascular Injuries of the Limbs: Fundamentals of Safe Application and Clinical Experience - Sivash, Iurii Iu.; Koval, Boris M. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Combat vascular injury of the limbs represents one of the most complex categories of trauma. Such injuries are rarely isolated and are often accompanied by extensive soft-tissue defects and microbial contamination, leading to severe complications such as thrombosis and erosive bleeding. Their treatment remains challenging, prolonged, and frequently results in limb loss. Negative pressure wound therapy (NPWT) has proven to be an effective method for managing complex gunshot wounds in combat conditions; however, evidence on its safe application in vascular limb trauma remains limited. Aim. To analyze theoretical and practical aspects of the safe use of NPWT in combat-related injuries of major limb vessels and to determine the indications, contraindications, and optimal technical parameters for its application. Materials and Methods. A comparative analysis of published data and clinical observations was performed, including cases of combat vascular injury of the lower limbs with associated soft-tissue defects where NPWT was used as part of staged surgical management. Results. Key indications, contraindications, and principles for safe NPWT use in vascular surgery were defined. The application of a two-layer dressing with a protective interface and continuous negative pressure of 70–80 mmHg ensured procedural safety in vascular reconstruction zones, promoted rapid wound cleansing and granulation, and enabled successful delayed closure using skin-grafting techniques. Conclusions. NPWT is an effective adjunct in the complex surgical management of combat vascular limb injuries combined with soft-tissue loss. Safe application requires reliable protection of the vascular anastomosis, maintenance of continuous negative pressure, and individualized risk assessment. Further research should focus on developing unified clinical protocols for NPWT in combat vascular trauma, including reliable vessel protection methods and prevention of procedure-related complications.